Advances in plant proteomics toward improvement of crop productivity and stress resistancex - Hu, Junjie; Rampitsch, Christof; Bykova, Natalia V. (Frontiers in Plant Science, 2015)
Abiotic and biotic stresses constrain plant growth and development negatively impacting crop production. Plants have developed stress-specific adaptations as well as simultaneous responses to a combination of various abiotic stresses with pathogen infection. The efficiency of stress-induced adaptive responses is dependent on activation of molecular signaling pathways and intracellular networks by modulating expression, or abundance, and/or posttranslational modification of proteins primarily associated with defense mechanisms. In this review, we summarize and evaluate the contribution of proteomic studies to our understanding of stress response mechanisms in different plant organs and tissues. Advanced quantitative proteomic techniques have improved the coverage of total proteomes and sub-proteomes from small amounts of starting material, and characterized post-translational modifications as well as protein–protein interactions at the cellular level, providing detailed information on organ- and tissue-specific regulatory mechanisms responding to a variety of individual stresses or stress combinations during plant life cycle. In particular, we address the tissue-specific signaling networks localized to various organelles that participate in stress-related physiological plasticity and adaptive mechanisms, such as photosynthetic efficiency, symbiotic nitrogen fixation, plant growth, tolerance and common responses to environmental stresses. We also provide an update on the progress of proteomics with major crop species and discuss the current challenges and limitations inherent to proteomics techniques and data interpretation for non-model organisms. Future directions in proteomics research towards crop improvement are further discussed.